Outcome comparison of lower trapezius tendon transfer and arthroscopic rotator cuff tear repair using muscle advancement for massive rotator cuff tear: a systematic review - Lang, Jun; Morya, Vivek Kumar; Noh, Kyu-Cheol (Clinics in shoulder and elbow, 2025)
This systematic review evaluates the clinical outcomes of two distinct, arthroscopic techniques for the surgical repair of massive rotator cuff tears; lower trapezius tendon transfer (LTT transfer) and muscle advancement (MA). Eleven studies, involving 433 patients, selected based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, were analyzed. The findings reveal that MA significantly improves functional outcomes, demonstrated by higher Constant-Murley scores (mean difference: 26.26 vs. 18.31, P<0.001), University of California, Los Angeles (UCLA) shoulder scores (14.95 vs. 8.3, P<0.001), acromiohumeral distance (AHD; 1.94 mm vs. 0.40 mm, P<0.001), and greater abduction recovery (46.48° vs. 31.86°, P=0.030). However, VAS (visual analog scale) score was better reduced in the LTT transfer groups i.e.-3.69 vs. -2.33, P<0.001., external rotation improvement (25.67° vs. 7.74°, P<0.001), and demonstrated lower retear rates (11.89% vs. 19.42%, P=0.031). The complication profiles differed between techniques: LTT transfer carried a higher risk of graft rupture (2.64% vs. 0%, P=0.031), while arthroscopic MA was associated with increased postoperative stiffness (2.91% vs. 0%, P=0.011). Based on these results, arthroscopic MA is recommended for younger, active patients with mobile residual tissue to optimize abduction and AHD restoration. In contrast, LTT transfer is better suited for cases involving massive defects requiring dynamic stabilization and external rotation recovery. These findings emphasize the importance of individualized surgical planning that considers tear severity, tissue viability, and patient functional demands. Despite limitations stemming from retrospective study designs and clinical heterogeneity, this review highlights the distinct clinical advantages and appropriate indications for both techniques.